HIV incidence and sexually transmitted disease prevalence associated with condom use - Sewankambo, Nelson (PubMed, 2001)
Objective: Evidence of condom effectiveness for HIV and sexually transmitted disease (STD) prevention is based primarily on high-risk populations. We examined condom effectiveness in a general population with high HIV prevalence in rural Africa. Methods: Data were from a randomized community trial in Rakai, Uganda. Condom usage information was obtained prospectively from 17 264 sexually active individuals aged 15±59 years over a period of 30 months. HIV incidence and STD prevalence was determined for consistent and irregular condom users, compared to non-users. Adjusted rate ratios (RR) of HIV acquisition were estimated by Poisson multivariate regression, and odds ratios of STDs estimated by logistic regression. Results: Only 4.4% reported consistent condom use and 16.5% reported inconsistent use during the prior year. Condom use was higher among males, and younger, unmarried and better educated individuals, and those reporting multiple sex partners or extramarital relationships. Consistent condom use signi®cantly reduced HIV incidence [RR, 0.37; 95% con®dence interval (CI), 0.15±0.88], syphilis [odds ratio (OR), 0.71; 95% CI, 0.53±0.94] and gonorrhea/Chlamydia (OR, 0.50; 95% CI, 0.25± 0.97) after adjustment for socio-demographic and behavioral characteristics. Irregular condom use was not protective against HIV or STD and was associated with increased gonorrhea/Chlamydia risk (OR, 1.44; 95% CI, 1.06±1.99). The population attributable fraction of consistent use for prevention of HIV was ÿ4.5% (95% CI, ÿ8.3 to 0.0), due to the low prevalence of consistent use in the population. Conclusions: Consistent condom use provides protection from HIV and STDs, whereas inconsistent use is not protective. Programs must emphasize consistent condom use for HIV and STD prevention. & 2
: a population study in Rakai, Uganda
Keywords: Africa; Condom; Effectiveness; HIV; Prevention; Sexually transmitted disease